A program based on Social Cognitive Theory and Smith's model of health and illness and its effect on maternal self-efficacy and child behavior - Sener, D. Konuk; Cimete, G. (Pergamon-Elsevier Science Ltd, 2016)
Purpose: This study was conducted in order to determine the effect of a program based on Social Cognitive Theory and Smith's Model of Health and Illness on the self-efficacy, self-esteem and attitudes of mothers and on the emotional and behavioral problems and competence levels of their children. Method: This quasi-experimental study used a control group and a pretest-posttest design. The sample was composed of 77 mothers (experimental group, n = 39; control group, n = 38) who had low self-efficacy and self-esteem and whose children had problematic behavior. The mothers in the experimental group underwent a 10-session program over a period of 10 weeks. This program included activities to help them build trust in themselves and their surroundings, induce positive thinking, increase their childcare knowledge and skills, establish an effective interaction with their children, set realistic and positive goals, cope with stress, experience the feeling of success and become motivated. Data were collected by using the Demographic Information Form, the self-efficacy for Parenting Task Index-Toddler Scale, the Rosenberg Self-Esteem Scale, the Parent Attitude Scale and the Brief Infant-Toddler Social & Emotional Assessment. Data were collected before the start of the program, immediately after its completion and three months afterwards. Results: It was found that, at the end of the program and after the following three months, the self-efficacy, self-esteem and democratic attitude scores of the experimental group mothers and the competency scores of their children had significantly increased compared to their pre-program scores. The problem domain scores of their children had decreased and a statistically significant difference was detected in favor of the experimental group. In both the experimental and the control group, a weak negative correlation was found between the self-efficacy and democratic attitude scores of the mothers and the problem domain scores of their children. Conclusion: The total 12-hour program created a positive change, even among the mothers with low self-efficacy, low self-esteem and low education and income levels who had problematic children. Therefore, healthcare professionals may find it beneficial to offer this program to all mothers having 2- and 3-year-old children. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Child development; Child behavioral problems; Maternal self-efficacy; Self-esteem; Parental attitudes